Werner clathrates: structure and selectivity - Wicht, Merrill (Department of Chemistry, 2017)
The development of enhanced selectivity of a host towards (aromatic) isomers continues to be an important feature in supramolecular studies. In this thesis, several nickel Werner complexes have been synthesised and used as crystallographic hosts with inclusions of aromatic isomers, polycyclic aromatic hydrocarbons, alcohols or ketones. Thermogravimetric methods were used to confirm the composition of the host-guest complexes and were employed to analyse their thermal behaviour. Structural features of the inclusion compounds were investigated using single crystal X-ray analysis and X-ray powder diffraction. Selectivity of the host towards binary or tertiary mixtures of guests has been scrutinised and the response determined by gas chromatography and nuclear magnetic resonance spectroscopy. The characteristics of the pyridine derivative ligands co-ordinated to the metal ion in the Werner complexes are instrumental in the behaviour of the inclusion compound. When the host Ni(NCS)₂(isoquinoline)₄ (H1) was exposed to xylene isomers the selectivity of the rigid isoquinoline ligand was investigated and compared to the more pliable 4-phenylpyridine. The flexibility of torsion angles in a range of pyridine derivative ligands was investigated to substantiate the findings for lack of selectivity with H1. Selectivity of H1 for the xylene isomers was determined for both the liquid and vapour phase binary mixtures of the guests using headspace gas chromatography for analysis. This was pursued with a mixed-ligand complex of both isoquinoline and 4-phenylpyridine to form the host Ni(NCS)₂(isoquinoline)₂(4-phenylpyridine)₂, H4. The crystal structures of this host with the three xylene isomers, ortho, meta and para-xylene (ox, mx and px, respectively) were analysed and the packing scrutinised. The arrangement of the ligands gave the new host flexibility to pack mx more intimately than the other two isomers hence the preferred selectivity outcome , i.e. mx>ox>px of this study. The single crystal structures of the Werner host, bis-isothiocyanato tetrakis-vinylpyridine nickel (II), H3, with seven polyaromatic hydrocarbons (PAHs), indene (IND), naphthalane (NAP), azulene (AZU), fluorene (FLU), anthracene (ANT), phenanthrene (PHE) and pyrene (PYR) were interpreted. Structural analysis revealed two types of crystal arrangements. The enhancement of green chemistry in the form of grinding, which avoids the use of solvents, slurrying and melt procedures was investigated. The success of inclusion compound formation by grinding was dependent on diffusion and the rate constant and half-life of the enclathration reaction were determined for the reactions between the host with two of the guests. The outcome of the crystallisation reaction and the grinding with this selected Werner host was the same; hence the preparation of these compounds via a more environmentally friendly solvent free or low solvent method has high potential. Werner hosts were designed and synthesized with so called 'sticky ligands', viz. coordinated aromatic groups with hydrogen bonding functionalities, with the aim to explore their inclusion formation properties. The synthesis of Ni(NCS)₂(nicotinamide)₄, H5, Ni(NCS)₂(isonicotinamide)₄, H6, and Ni(NCS)₂(nicotinamide)₂(isonicotinamide)₂, H7, whose functional groups form amide synthons, generated specific packing patterns which were examined in this thesis. Guests such as amides, alcohols and ketones were located in positions, either in voids or in layers, between the host sheets. Three dimensional packing arrangements were observed and are discussed in the H6 and H7 structures. The thesis is aimed to present and discuss the selected Werner complexes and their inclusion formation properties. The obtained supramolecular systems have shown a great variety of structural features which can be altered on a systematic manner.